2009
DOI: 10.1111/j.1741-3729.2008.00537.x
|View full text |Cite
|
Sign up to set email alerts
|

For Richer, for Poorer: Money as a Topic of Marital Conflict in the Home

Abstract: Guided by a family stress perspective, we examined the hypothesis that discussing money would be associated with the handling of marital conflict in the home. Analyses were based on dyadic hierarchical linear modeling of 100 husbands’ and 100 wives’ diary reports of 748 conflict instances. Contrary to findings from previous laboratory-based surveys, spouses did not rate money as the most frequent source of marital conflict in the home. However, compared to non-money issues, marital conflicts about money were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
221
0
14

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(243 citation statements)
references
References 29 publications
8
221
0
14
Order By: Relevance
“…The psychology literature has suggested that distress arising from financial worries can affect partners' interaction patterns and increase interpersonal conflict (Bradbury, Fincham, & Beach, 2000;Neff & Karney, 2009). For example, when couples argue over money, their conflicts are typically more intense and recurrent than arguments that concern other topics (Papp, Cummings, & Goeke-Morey, 2009). Compounding this is the fact that low earnings often co-occur with living in a highpoverty neighborhood, health problems, and other traumatic events, and these factors can have a cumulative effect on relationship satisfaction (Rauer, Karney, Garvan, & Hou, 2008).…”
mentioning
confidence: 99%
“…The psychology literature has suggested that distress arising from financial worries can affect partners' interaction patterns and increase interpersonal conflict (Bradbury, Fincham, & Beach, 2000;Neff & Karney, 2009). For example, when couples argue over money, their conflicts are typically more intense and recurrent than arguments that concern other topics (Papp, Cummings, & Goeke-Morey, 2009). Compounding this is the fact that low earnings often co-occur with living in a highpoverty neighborhood, health problems, and other traumatic events, and these factors can have a cumulative effect on relationship satisfaction (Rauer, Karney, Garvan, & Hou, 2008).…”
mentioning
confidence: 99%
“…These outside ratings address an important question but overlook the possibility that the same topic will not be equally easy or difficult for all couples. Finally, Papp et al (2009) and Rehman et al (2011) focused only on certain topics (money and sex, respectively) in comparison with all other topics combined, thus obscuring information about these other topics.…”
mentioning
confidence: 99%
“…With respect to discussion topics, certain relationship problems may inspire worse communication than others. For example, a diary study in which 100 couples sampled from the community reported on each instance of marital conflict they had over a 15-day period found that conflicts about money elicited more self-reported angry and depressive behavior than did conflicts about other topics (Papp, Cummings, & Goeke-Morey, 2009). Additionally, a study in which 15 community couples were directed by researchers to discuss their most contentious sexual and nonsexual conflicts indicated that sexual topics are much more difficult for couples to discuss than nonsexual topics (Rehman et al, 2011).…”
mentioning
confidence: 99%
“…Mais concretamente, investigação prévia tem indicado que a aumentada sintomatologia depressiva nos pais pode estar negativamente relacionada com o funcionamento familiar (Conde, Figueiredo, & Bifulco, 2011;Foster et al, 2008;Keitner, Ryan, Kohn, Bishop, & Epstein, 1995), o aumento do conflito conjugal e o menor envolvimento parental (Cummings, Keller, & Davies, 2005). Características só-cio-demográficas parecem também contribuir para a predição do ajustamento familiar, tais como a idade (e.g., Pacheco, Costa, & Figueiredo, 2009) e os recursos financeiros (R. Conger, K. Conger, & Martin, 2010;Hilton & Kopera-Frye, 2004;Papp, Cummings, & Goeke-Morey, 2009). …”
Section: Factores Individuais Diádicos E Sistémicos No Ajustamento Punclassified